(untitled) (Universal International Scientific Journal, 2026)
This article examines the improvement of methodology for developing the personal and professional qualities of future preschool teachers. It explores the importance of professional orientation, communicative and moral qualities of teachers, as well as the role of competency-based, activity-based, and student-centered approaches in training preschool education specialists.